The Ontological Basis and Justification of Law - Michael M Uzomah (Universitas Negeri Makassar, 2021)
This paper responds to the linchpin and central problem of jurisprudence in all its variants (legal schools) which is the task of establishing the meaning, nature and validity of law. The notion of validity and obligation is not only crucial to the concept of law, but also essentially inalienable. In the naturalist perception of law as well as in the positivist explication of law, the notion of validity is given fundamental attention. However, the point of disagreement or conflict, between legal naturalism and legal positivism (which are the two most outstanding and contending legal thoughts) revolves around the question: Where exactly does or from where does the law acquire its obligatory or binding or legal force? Differently put, in what does the validity of the law subsists? What invests a legal stamp or seal on a piece of legislation? Or what confers legality on legal norms that justifies and commands their obedience? While the naturalist appeal to some extra-legal, moral and metaphysical elements as the foundation of the binding force and validity of law (the oughts), the legal positivist took a formal and empirical approach to the explanation of the obligation and validity of law (law as it is, without recourse to metaphysical or moral oughts, is valid and commands unconditional obedience). Consequently, as an attempt towards establishing the ontological nature and justification of law, this paper defends the naturalist jurisprudence. The paper argues that to properly configure the true nature of positive laws otherwise called the jurisprudential laws in relation to law per se, the philosopher transcend the formalistic and materialistic study of law (empirical and descriptive) to the transcendental (prescriptive) examination of law not just in its ontological descriptive dimension, but most essentially in relation to its normative or prescriptive form. In lieu, the paper further argue that consequent upon the prescriptive nature of the law of nature, and the concomitant rational nature of man, positive laws cannot but inexorably be morally biased. The methods adopted by the research include the expository analytic and prescriptive methods.